All-stage targeted therapy for invasive cryptococcosis through interaction between the secretory protein Cig1 and hemin - Liting Cheng; Zhongyi Ma; Xinlin Yang; Xue Wang; Yuqiong Wang; Xinlong Liu; Zhongjie Tang; Dingxi Jang; Guojian Liao; Tongbao Liu; Shuang Wu; Chong Li (Asian Journal of Pharmaceutical Sciences, 2025)
Cryptococcosis, a serious systemic fungal infection caused by Cryptococcus neoformans (C. neoformans) and its variants, poses a significant clinical challenge due to its poor prognosis and severe health implications. The treatment of cryptococcal infections is complicated by several unique factors, stemming from both the pathogenic characteristics of the fungi and the biological barriers they exploit. These include the fungi's protective capsule, their ability to reside within host macrophages—thereby evading pharmacological intervention—and their involvement in multi-organ infections such as the lung and brain, in particular their strategic positioning within the brain, protected by the blood-brain barrier (BBB). To overcome these obstacles, precise active targeting emerges as a pivotal strategy. Identifying common targets is imperative to enhance therapeutic efficacy while ensuring the druggability of delivery systems. However, research on the methodology for selecting such shared targets remains sparse. In our investigation, we have pioneered the use of secreted proteins as shared target to trace the pathogens and their infection pathways. We identified the mannoprotein Cig1, prominently expressed on the surfaces of infected macrophages, lungs, and brains, as a viable shared target. On this basis, we utilized Hemin, a ligand for Cig1, to design liposomes (Hemin Lip) tailored for addressing complex fungal infections. By leveraging the interaction with the secreted protein Cig1, Hemin Lip specifically identifies and binds to organs and macrophages harboring cryptococcal infections, thereby facilitating targeted and efficacious clearance of both intracellular and extracellular fungus. Moreover, we have extended this targeting mechanism to other nanomedicinal platforms, including albumin nanoparticles. This study proposes an innovative drug delivery model that targets extracellular secretory proteins within the infection microenvironment, offering a streamlined formulation with the potential for effective therapy against complex infections.